Ulysses in Focus : Genetic, Textual, and Personal Views - Groden, Michael (Book collections on Project MUSE., 2010)
Bringing together 12 essays in 3 areas of Joyce criticism and scholarship, this book offers various personal adventures from a life lived with Joyce's work. It connects these scholarly developments and contretemps to the author's personal history and provides fascinating new genetic readings of several episodes of 'Ulysses' that advance our understanding of the novelAEs composition.